Environmental health sciences decision making : risk management, evidence, and ethics : workshop summary - Coble, Yank D.; Coussens, Christine; Quinn, Kathleen (Kathleen Kolar) (Online access: NCBI NCBI Bookshelf., 2009)
"Environmental health decision making can be a complex undertaking, as there is the need to navigate and find balance among three core elements: science, policy, and the needs of the American public. Policy makers often grapple with how to make appropriate decisions when the research is uncertain. The challenge for the policy maker is to make the right decision with the best available data in a transparent process. The workshop, summarized in this volume, included an overview of the principles underlying decision making, the role of evidence and challenges for vulnerable populations, and ethical issues of conflict of interest, scientific integrity, and transparency. The workshop engaged science interest groups, industry, government, and the academic sector."--Publisher's description